Valley-conserved topological integrated antenna for 100-Gbps THz 6G wireless - Jia, Ridong (2024)
The topological phase revolutionized wave transport, enabling integrated photonic interconnects with sharp light bending on a chip. However, the persistent challenge of momentum mismatch during intermedium topological mode transitions due to material impedance inconsistency remains. We present a 100-Gbps topological wireless communication link using integrated photonic devices that conserve valley momentum. The valley-conserved silicon topological waveguide antenna achieves a 12.2-dBi gain, constant group delay across a 30-GHz bandwidth and enables active beam steering within a 36° angular range. The complementary metal oxide semiconductor-compatible valley-conserved devices represent a major milestone in hybrid electronic-photonic-based topological wireless communications, enabling terabit-per-second backhaul communication, high throughput, and intermedium transport of information carriers, vital for the future of communication from the sixth to X generation.